Answers

2016-07-11T23:48:45+08:00
1.) 6x^2 - 24 = 0
     6x^2 = 24 (Divide by 6)
     x^2 = 4 (Square root)
     x = (Positive Negative) 2
2.) x^2 - 16 = 0
     x^2 = 16
     x^2 = 4
     x = (Positive Negative) 4
3.) 2x^2 - 98 = 0
     2x^2 = 98
     x^2 = 49
     x = (Positive Negative) 7
4.) 2(x-3)^2 = 18
     x - 3 =  (Positive Negative) 1 (Square Root Of) 18
     x = 3 (Positive Negative) 1 (Square Root Of) 18
     x = 3 + 1 (Square Root Of) 18       x = 3 - 1 (Square Root Of) 18
     x = 4 (Square Root Of) 18     x = 2 (Square Root Of) 18
5.) (3x - 2)^2 = 144
     3x - 2 = 12
     3x = 2 (Postive Negative) 12
     3x = 2 + 12      3x = 2 - 12
     3x = 14            3x = -10
     x = 4.67           x = -3.34

Im not sure in number 4 and 5 :(
1 5 1